2014
DOI: 10.3324/haematol.2014.119537
|View full text |Cite
|
Sign up to set email alerts
|

Role of the clathrin adaptor PICALM in normal hematopoiesis and polycythemia vera pathophysiology

Abstract: ABSTRACTobtain targeted mutation of Picalm in non-agouti black Bruce4 C57BL/6-Thy1.1 mouse embryonic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 52 publications
1
46
0
1
Order By: Relevance
“…We therefore sought to compare Sf3b1 +/+ and Sf3b1 +/K700E erythroblast maturation using an in vitro culture system that closely mimics the in vivo terminal proliferation and maturation of erythroid cells. Equal numbers of c-Kit + HSPCs were isolated from the bone marrow of Sf3b1 +/+ and Sf3b1 +/K700E mice, and the cells were cultured in the presence of cytokines that induce erythroid differentiation (Ishikawa et al, 2014). Although both the Sf3b1 +/+ and Sf3b1 +/K700E HSPCs differentiated in culture, the total number of cells (Figure 2D) and the absolute number of cells at each stage of erythroid maturation (Figure 2E) were significantly lower in cells derived from the Sf3b1 +/K700E animals compared to Sf3b1 +/+ animals.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore sought to compare Sf3b1 +/+ and Sf3b1 +/K700E erythroblast maturation using an in vitro culture system that closely mimics the in vivo terminal proliferation and maturation of erythroid cells. Equal numbers of c-Kit + HSPCs were isolated from the bone marrow of Sf3b1 +/+ and Sf3b1 +/K700E mice, and the cells were cultured in the presence of cytokines that induce erythroid differentiation (Ishikawa et al, 2014). Although both the Sf3b1 +/+ and Sf3b1 +/K700E HSPCs differentiated in culture, the total number of cells (Figure 2D) and the absolute number of cells at each stage of erythroid maturation (Figure 2E) were significantly lower in cells derived from the Sf3b1 +/K700E animals compared to Sf3b1 +/+ animals.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of the clathrin adaptor protein, PICALM, was identified in two ENU mutants displaying significant anaemia due to defects in iron metabolism (Potter et al, 1997;Klebig et al, 2003). Similarly, Picalm knockout mice (Suzuki et al, 2012) and conditionally deleted haematopoietic Picalm mice (Ishikawa et al, 2015) demonstrated impaired iron uptake in erythroid cells due to deficient TfR-mediated endocytosis. Studies in these animals demonstrated a cellular-specific effect for regulation by endocytosis given that myeloid and lymphoid lineages were largely unaffected by Picalm deficiency, consistent with our findings in Dnm2 V235G animals and, indeed, other studies involving disease-specific pathogenesis of DNM2 mutations in human CNM and CMT (Koutsopoulos et al, 2011;Bohm et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Even though RNAi-based depletion of CALM in HeLa cells led to larger and more irregularly formed Clathrin-coated pits [111,112], Transferrin uptake was either normal [111] or only partially affected [110]. Also the analysis of AP180/CALM deficient mouse embryonic fibroblasts revealed only modest effects on Clathrin-coated pit dynamics [113]. These experimental data led to the hypothesis that, even though AP180/CALM are together with Clathrin and AP-2 the most abundant components of Clathrin-coated vesicles [110], they are not essential for general endocytosis.…”
Section: Ap180 and Calmmentioning
confidence: 99%
“…However, the physiological relevance of these additional interactions is presently largely unclear apart from the fact that missorting of VAMP3 and VAMP8 was linked to defects in autophagy [123]. Instead, the analysis of CALM-deficient mouse models [113,124] revealed first of all an essential role for CALM in the sorting of the TfR, specifically in red blood cell precursors, even though the molecular basis for this interaction and its cell-type specificity is not resolved yet. Thus, constitutive CALM KO mice suffer from embryonal or early postnatal lethality, presumably due to deficient Transferrin uptake in erythroid cells and a resulting anemia [113,124].…”
Section: Lessons From Ap180-and Calm-deficient Mouse Modelsmentioning
confidence: 99%